1981
DOI: 10.2172/6254123
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of crystal densities of organic explosives by group additivity

Abstract: d i s tr i b u ti o n o f t h i s d o c u m e n t i s u n lim ite d An AHirmative Action/Equal Opportunity Employer rf-1 ' This work was supported by the US Department o f Energy and the Naval Surface Weapons Center under project order number N6092I-80-W R-W 0165. Edited by Katherine H. Harper Photocom position by Alice Creek D IS C IJ tlM E R This report was prepared as an account o f w ork sponsored by an agency o f the U nited States Ckrvemment. N either the U nited States G overnm ent nor any agency th ere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 4 publications
4
62
0
Order By: Relevance
“…As part of a program aimed at finding insensitive, high-performance explosive molecules we have prepared 1-methyl-2,3,4,5-tetranitropyrrole (I) and now report its crystal structure. Stine's (1981) method gives 1.83 g cm -~ for the density of (I), in good agreement with D x.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…As part of a program aimed at finding insensitive, high-performance explosive molecules we have prepared 1-methyl-2,3,4,5-tetranitropyrrole (I) and now report its crystal structure. Stine's (1981) method gives 1.83 g cm -~ for the density of (I), in good agreement with D x.…”
supporting
confidence: 65%
“…Therefore, in searching for better explosives, high density is one of the desired properties. Stine (1981) has devised an empirical method of density prediction based *This work was performed under the auspices of the US Department of Energy.…”
mentioning
confidence: 99%
“…However, our prediction is somewhat low compared with the previous studies by Korkin and Bartlett 2 and by Gejji et al 41 Both studies utilized the group additivity method, but they employed different sets of parameters. Korkin and Bartlett predicted the density of TNTA to be 2.1 g/cm 3 , and Gejji et al, who utilized the group parameters developed by Stine,42 predicted to be 2.27 g/cm 3 . We believe that the substantial overestimation by Gejji et al is attributed to Stine's parameters.…”
Section: Explosive Performance Of Nitro-substituted Triazines Derivatmentioning
confidence: 99%
“…Researchers have tried to generate an ability to predict, with satisfactory accuracy, the crystal densities of proposed new energetic compounds, for example by invoking atom/group volume additivities [8,9] or by modelling the crystal structures [10,11]. Kim et al have suggested that a prediction that differs by less than 0.03 g/cm 3 from the experimental value should be defined as 'excellent', while one that is between 0.03 and 0.05 g/cm 3 in error is still 'informative' [12].…”
Section: Introductionmentioning
confidence: 99%
“…For estimating the crystal density of available energetic materials, various methods have been developed. These include electrostatic potentials using quantum-mechanically determined molecular volumes [11][12][13][14][15], group additivities [8,9,[16][17][18], empirical methods [19][20][21][22] and Quantitative Structure-Property Relationships (QSPR) [23].…”
Section: Introductionmentioning
confidence: 99%